Towards sustainable environment in Somalia: the role of conflicts, urbanization, and globalization on environmental degradation and emissions - Warsame, Abdimalik Ali; Hassan Abdi, Abdikafi; Amir, Amir Yahya; Azman-Saini, W.N.W. (Elsevier, 2023)
Climate change is a global phenomenon in the 21st century. Hence, achieving environmental sustainability has become a global initiative to tackle the repercussions of climate change. Fossil fuel energy consumption and economic growth remain critical amidst environmental degradation and emissions. Contrary to the previous attempts, this study examines the impacts of conflicts “ internal and external “, urbanization, and globalization on environmental degradation and emissions in Somalia. The autoregressive distributed lag (ARDL) model, kernelized regularized least squares (KRLS) machine learning method, and vector error correction modeling (VECM) method are utilized with annual time series data spanning 1985“2016. The empirical results show that external conflict, globalization, and urbanization increase environmental degradation in the long run but not in the short run, except globalization which has a constructive role in enhancing environmental quality in the short-run. Notably, internal conflict is inconsequential both in the short- and long-run. The results of the study are robust for various analysis methods and environmental pollution indicators. In contrast, the VECM results indicate that urbanization, economic growth, and internal and external conflicts Granger cause environmental degradation both in the short and long-run, whereas globalization causes environmental degradation in the short run only. Notably, there is bidirectional causality between urbanization and environmental degradation in the short run only. A striking result is that both internal and external conflicts are neither caused by environmental degradation nor other regressors in the short- and long-run. Hence, relevant policy implications are suggested based on the empirical findings of the study.